The Impact Of Macroeconomic Variables On The Jakarta Islamic Index (ISSI) And LQ45 Index - Wijayanti, Ning; Trisnafi, Kukuh; Aqim Adlan, Muhammad (El-kahfi | Jurnal Ekonomi Islam, 2025)
This study investigates the influence of key macroeconomic variables—namely inflation, interest rate, and exchange rate—on the performance of the Indonesia Sharia Stock Index (ISSI) and the LQ45 Index during the period January 2022 to December 2024. Using a quantitative approach with multiple linear regression analysis, the research examines how Islamic and conventional equity markets in Indonesia respond differently to macroeconomic shocks. The findings reveal that the LQ45 Index is significantly influenced by inflation (positive) and interest rates (negative), while the ISSI is significantly affected only by exchange rate fluctuations (positive). These contrasting sensitivities reflect structural and ethical distinctions in index composition and investor behavior. From an Islamic economics perspective, the study supports the resilience of shariah-compliant firms rooted in real-sector activities and low debt exposure, in alignment with the principles of maqashid shariah—particularly wealth preservation (hifz al-mal) and the prohibition of riba. This research contributes to the growing literature on Islamic financial markets by highlighting the macroeconomic behavior of Islamic stock indices and offering practical insights for policymakers, portfolio managers, and investors in dual financial systems.